2(3-x)=3(x-4)+15

Simple and best practice solution for 2(3-x)=3(x-4)+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3-x)=3(x-4)+15 equation:


Simplifying
2(3 + -1x) = 3(x + -4) + 15
(3 * 2 + -1x * 2) = 3(x + -4) + 15
(6 + -2x) = 3(x + -4) + 15

Reorder the terms:
6 + -2x = 3(-4 + x) + 15
6 + -2x = (-4 * 3 + x * 3) + 15
6 + -2x = (-12 + 3x) + 15

Reorder the terms:
6 + -2x = -12 + 15 + 3x

Combine like terms: -12 + 15 = 3
6 + -2x = 3 + 3x

Solving
6 + -2x = 3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6 + -2x + -3x = 3 + 3x + -3x

Combine like terms: -2x + -3x = -5x
6 + -5x = 3 + 3x + -3x

Combine like terms: 3x + -3x = 0
6 + -5x = 3 + 0
6 + -5x = 3

Add '-6' to each side of the equation.
6 + -6 + -5x = 3 + -6

Combine like terms: 6 + -6 = 0
0 + -5x = 3 + -6
-5x = 3 + -6

Combine like terms: 3 + -6 = -3
-5x = -3

Divide each side by '-5'.
x = 0.6

Simplifying
x = 0.6

See similar equations:

| -9f=96-f | | 2(2-x)=3(x-4)+15 | | -6x+12=6x-12 | | 2a(a+5)-a(a-6)= | | t(t)=2(7t-24) | | 2(7t-24)=t(t) | | 3(2x+9)=-28+31 | | 8x+22=5x+13 | | 5x+7=2x+13 | | -2x+4=-5 | | 2(5b-1)=7b+7 | | 5y-6=-7 | | 12n=11n+27 | | 10a+4b+7a+10b-17a-14b= | | 4a-12=-8 | | -x+12=5 | | 8x-19=2x+47 | | 4(x-3)+x=18 | | x=14 | | -3x+5=4 | | 12+7x+x^2= | | 14+16=x | | 10a+4b-a+5b= | | 12x-8+2x-5=11x-3+2x | | 5.98t=1.38t-460 | | 7x-3=5x+12 | | 2x+9=7x+10 | | 2x^3+2x^2+x+1=0 | | 4y^2=81 | | 7=-16t^2+16+3 | | 4x+12=6(x-1) | | 4x+12=6(x-1) |

Equations solver categories